Incidence and evolutionary relevance of autotriploid cytotypes in a relict member of the genus Daphne (Thymelaeaceae) - Gajdošová, Zuzana; Svitok, Marek; Cetlová, Veronika; Mártonfiová, Lenka; Kučera, Jaromír; Kolarčik, Vladislav; Hurdu, Bogdan-Iuliu; Sîrbu, Ioana-Minodora; Turisová, Ingrid; Turis, Peter; Slovák, Marek (AoB PLANTS, 2023)
Odd ploidy-level cytotypes in sexually reproducing species are considered a dead end due to absent or reduced fertility. If sterility is only partial, however, their contribution to the population gene pool can be augmented by longevity and clonal growth. To test this, we investigated the cytotype origin and spatial pattern, and pollen viability in three relict shrub species of the genus Daphne (Thymelaeaceae Juss.) in central Europe. Daphne cneorum subsp. cneorum is a widespread European species that has a broad ecological amplitude, whereas D. cneorum subsp. arbusculoides and D. arbuscula are narrow endemics of the western Pannonian Plain and the Western Carpathians, respectively. Our study confirmed that all three taxa are diploid. However, of more than a thousand analysed individuals of D. cneorum subsp. cneorum, five in four different populations were triploid. Our data indicate that these triploids most likely originate from recurrent autopolyploidization events caused by the fusion of reduced and unreduced gametes. High pollen viability was observed in all three taxa and in both diploid and triploid cytotypes, ranging from 65 to 100 %. Our study highlights the significant role of odd ploidy-level cytotypes in interploidy gene flow, calling for more research into their reproduction, genetic variability, and overall fitness. Interestingly, while the endemic D. arbuscula differs from D. cneorum based on genetic and genome size data, D. cneorum subsp. arbusculoides was indistinguishable from D. cneorum subsp. cneorum. However, our study reveals that the subspecies differ in the number of flowers per inflorescence. This is the first comprehensive cytogeographic study of this intriguing genus at a regional scale, and in spite of its karyological stability, it contributes to our understanding of genomic evolution in plant species with a wide ecological amplitude.
Keywords: Daphne; genome size stasis; endemics; triploids; pollen fertility; Pannonian Basin; Carpathians; relicts; ITS; polyploidy